Simulation of the two-phase liquid – gas flow through ultrasonic transceivers application in ultrasonic tomography - Zulkarnay, Zakaria (International Frequency Sensor Association (IFSA), 2010)
Link to publisher's homepage at http://www.sensorsportal.com/